ANALISIS KESULITAN BELAJAR ANAK AUTIS PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN CACAH SMPLB PONTIANAK - K, Tri Nataline; R, Zubaidah; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research wants to look at learning difficulties and the cause of learning difficulties for autistic chidren in the addition and subtraction of whole number in SMPLB Bina Anak Bangsa Pontianak. This research is a descriptive research with a qualitative approach. Subject in this research were 3 out of 5 children with class IX SMPLB Bina Anak Bangsa Pontianak selected based on test results. The object of this research is the learning difficulties experienced by children with autism. Data collection techniques using observation, written tests and interviews. Data collection tools such as observation sheets, learning outcomes tests and interview guidelines to explore deeper the difficulties and causes of learning difficulties for autistic children. The results showed the learning difficulties of autistic children who appeared in mathematics learning the addition and subtraction of whole numbers 1) difficulty in the concept of the addition of identities, 2) difficulty in the concept of subtraction using the countdown method, 3) difficulties in using borrowing methods in reduction operations, 4) difficulty in understanding questions in the form of stories. The cause of learning difficulties in learning mathematics is the addition and subtraction of whole numbers 1) the lack of variations of housing questions given, 2) the lack of practice questions in the borrowing method, 3) the story problems in the learning of the addition of enumeration numbers are less relevant, and 4) the teacher gives a less varied practice of story questions. Keywords: Alphabetic Order, Bold, Capitalize Each Word, Font 11